Bibliometric denialism - Torres-Salinas, Daniel (Anuario ThinkEPI, 2023)
This text discusses and denounces the growing trend of "bibliometric denialism," which rejects the utility of bibliometric indicators in scientific evaluation. This denialism is evident in the decision to dispense with metrics, a practice encouraged by the Declaration on Research Assessment (Dora) and, especially, upon the signing of the Agreement on Reforming Research Assessment promovido promoted by the Coalition for Advancing Research Assessment (Coara). Both advocate for a more qualitative approach, primarily based on peer review. However, we argue that these qualitative approaches have been adopted without considering their limitations and ignoring the principles and methods of evaluative bibliometrics.
Keywords: Evaluative bibliometrics; Scientific policy; Peer review; Bibliometric indicators; Dora; Coara